Transformative Islamic Education at Islamic Boarding School in South Tapanuli - Muhammad Darwis Dasopang; Suheri Sahputra Rangkuti; Hilman Rizky Hasibuan; Kimlansyah Romadan Siregar (STAI Hubbulwathan Duri, 2023)
Islamic Boarding School as an Islamic educational institution initially only taught religious knowledge. However, currently some Islamic Boarding School in Indonesia are trying to transform by adopting science education and even more focused on studying science. This is interesting because as a newcomer, the presence of Islamic Boarding School that has been transformed into a science boarding school is in great demand by the people of South Tapanuli. This research seeks to answer the paradigm that underlies the transformation, the underlying reasons and the purpose of the change. Methodologically, to read and analyze paradigm shifts in several Islamic boarding schools in South Tapanuli, this study uses an integration approach. Meanwhile, to capture the reasons that underlie the paradigm change and the purpose of the change, this research uses a qualitative method with a descriptive approach. The results of this study found that the transformative paradigm of science-religion is the paradigm that underpins the change. An important reality behind the transformation is the assumption that the Islamic boarding that existed so far has lost its dimension of reality. The main goal of the paradigm shift is to balance and revitalize science knowledge in educational institutions.